Mitochondrial DNA 4977 bp Deletion in Peripheral Blood Is Associated With Polycystic Ovary Syndrome - Ye, Mujin; Hu, Bin; Shi, Weihui; Guo, Fei; Xu, Chenming; Li, Shuyuan (Frontiers in Endocrinology, 2021)
Background Polycystic ovary syndrome (PCOS) is a common endocrine disorder worldwide. We aimed to examine the associations of two mitochondrial DNA (mtDNA) biomarkers in the peripheral blood, mtDNA copy number (CN) and mtDNA4977 deletion rate (DR), with PCOS in a clinical setting. Methods We performed a study involving 263 women with PCOS and 326 age-matched controls between June 2015 and June 2019. The mtDNA CN and mtDNA4977 DR were measured using multiplex probe-based qPCR. The associations of the mtDNA CN and mtDNA4977 DR with the risk of PCOS were estimated using logistic regression. Results Analysis of the associations between mtDNA biomarkers and PCOS indicate that the mtDNA CN (P = 0.003) and mtDNA4977 DR (P < 0.001) in PCOS patients were significantly higher than those in the controls. After adjusting for the body mass index, luteinizing hormone/follicle-stimulating hormone ratio, and testosterone level, only higher mtDNA4977 DR was associated with PCOS (odds ratio 1.053, 95% confidence interval 1.024 to 1.083; P < 0.001). The linear dose-response trends of the mtDNA4977 DR were also supported by the quartile analysis. Conclusion Multivariable models suggest that mtDNA4977 DR levels are strongly associated with PCOS and represent an independent risk factor for PCOS. Further investigation of the utility of mtDNA as a biomarker for PCOS is warranted.